CRISPR/CAS9 KNOCKOUT OF THE TAM RECEPTOR TYRO3 IS AN APPROACH TO OVERCOME BLADDER CANCER CHEMORESISTANCE - Anuarbekova, Aruzhan (Nazarbayev University School of Medicine, 2025)
In Kazakhstan, bladder cancer ranks eleventh among the causes of death from cancer. The lack of effective therapy in Kazakhstan makes it a subject of close attention for researchers. Despite considerable advances in research, resistance to chemotherapy remains a considerable challenge in the therapeutically effective treatment of bladder cancer. TYRO3 TAM receptor knockout may exert anti-cancer effects by weakening cancer cell resistance to chemotherapy. TYRO3 is an extracellular TAM receptor that regulates various physiological processes, including cell survival, maintenance of homeostasis, and cellular immunity. The receptor is activated when ligands Gas6 and Protein S bind to the extracellular domain. It causes the dimerization of the receptor, resulting in autophosphorylation of kinase domains to activate intracellular signaling pathways like PI3K/AKT, MAPK/ERK, and STAT, and regulate gene expression. Dysregulation of the TYRO3 receptor contributes to cancer development, growth, and metastasis due to the upregulation of several oncogenic pathways. Overexpression, gene amplification, and overactivation of TYRO3 are often associated with cell survival, metastasis, and resistance to chemotherapy. Also, effects on innate immune cells contribute to the suppression of antitumor immunity and resistance to immune checkpoint inhibitors. Genetic deactivation of tumor-associated receptors using the CRISPR/Cas9 knockout method, based on sgRNA-mediated nuclease targeting, has potential in anticancer therapy. The project uses a knockout system with low off-target effects and high efficiency to deactivate TYRO3. Knockout of TYRO3 may lead to lower tumor growth, enhanced chemotherapy sensitivity, and possibly reduced metastasis. Deletion of TYRO3 may also contribute to the efficacy of immunotherapy by reducing immune suppression and boosting the antitumor immune response. This thesis aims to knock out the TYRO3 tyrosine kinase receptor in bladder cancer cell lines using CRISPR/Cas9 and to better understand how TYRO3 affects the development, growth, and response of cancer cells to treatment.
Keywords: Bladder cancer; BC; NMI; MI; non-muscle invasive; muscle-invasive; TYRO3; TAM receptor; CRISPR/CAS9; knockout; chemoresistance; Gas6; Protein S.; Type of access: Open